Clinical Application of Individualized Pulmonary Bi-Orifice for the Reconstruction of Right Ventricular Outflow Tract in Tetralogy of Fallot - Wu, Ming; Fan, Chengming; Liu, Jian; Iroegbu, Chukwuemeka Daniel; Chen, Wangping; Huang, Peng; Tang, Mi; Wu, Xun; Wang, Chunle; Xiang, Kun; Zhou, Wenwu; Yang, Jinfu (Frontiers in Cardiovascular Medicine, 2021)
Objective: The study aims to establish a new method in the Tetralogy of Fallot (ToF) called the pulmonary valve bi-orifice method (pulmonary annular sparing with an individualized autologous pericardial patch; thus, two orifices are formed at the level of the pulmonary valve annulus) to reconstruct the right ventricular outflow tract (RVOT). Methods: A retrospective analysis of 128 TOF patients from October 2009 to June 2018 with severe pulmonary valve dysplasia who underwent transvalvular annular patch (TAP) procedure (control group) or an individualized pulmonary valve bi-orifice procedure (observation group) were studied. The RVOT for each patient in the observation group was individually reconstructed per the patient's weight and the size of the autologous pulmonary valve using the bi-orifice method; however, increasing the cross-sectional area of the pulmonary valve annulus without destroying its integrity. The result was then compared to the control group, where TAP procedures were applied to evaluate the short to mid-term outcome(s). An in vitro simulation test was used to verify the anti-regurgitation mechanism of the new method. Results: The in vitro simulation test indicated that the anti-regurgitation mechanism was completed by the pericardial patch and the autologous pulmonary valve movement toward each other. Thus, for clinical applications, patients in both groups were compared. The results showed no significant differences in cardiopulmonary bypass and aortic cross-clamp time, mechanical ventilation, and ICU and post-operative residence between the two groups. During the follow-up period (3- to 12-years), 14 patients in the observation group had mild regurgitation after surgery (22.2%), while 10 patients had moderate pulmonary regurgitation (15.8%) with no right ventricular (RV) dilation. On the other hand, 22 patients (39.6%) had moderate to severe regurgitation in the control group, while left pulmonary artery stenosis occurred in one patient. In the control group, six patients (9.2%) with severe RV dilation were reoperated. Conclusion: Individualized pulmonary valve bi-orifice procedure is a safe and excellent method for reconstructing RVOT in ToF.